2022
DOI: 10.3390/youth2040040
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Hostile Attitudes in and through Education—Transformative Ideas from Finnish Youth

Abstract: Amid global disturbances, the calls for educational institutions to promote peace and counter hostility intensify. However, policymakers and other adults typically draft the various programs developed for schools to pursue this mission. While young people have valuable insights into the realities and issues around them, their ideas are rarely solicited in this respect. This study contributes towards filling this gap by bringing insights from Finnish youth on how to address hostile attitudes and foster the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Shifts in affiliations and national identities were also visible in our previous study where Finnish youth ( n = 2873) indicated more appreciation for universal, human rights-based values than for nationality (Koirikivi et al, 2021). Moreover, our studies on Finnish youths’ prejudices (survey n = 2200) and their justifications of othering ( N = 45 interview accounts) showed that their negative attitudes are not based on traditional social categories, such as ethnicity or religion, but on individual differences between lifestyles and behaviors that they perceived as threatening their feelings of safety and social harmony (Koirikivi et al, 2021; Benjamin et al, accepted, 2022c). However, there is still a notable gap in research on Finnish youth’s intergroup mindsets as well as their own definitions of ingroups and outgroups.…”
Section: Mindset Associated With Extremismmentioning
confidence: 88%
“…Shifts in affiliations and national identities were also visible in our previous study where Finnish youth ( n = 2873) indicated more appreciation for universal, human rights-based values than for nationality (Koirikivi et al, 2021). Moreover, our studies on Finnish youths’ prejudices (survey n = 2200) and their justifications of othering ( N = 45 interview accounts) showed that their negative attitudes are not based on traditional social categories, such as ethnicity or religion, but on individual differences between lifestyles and behaviors that they perceived as threatening their feelings of safety and social harmony (Koirikivi et al, 2021; Benjamin et al, accepted, 2022c). However, there is still a notable gap in research on Finnish youth’s intergroup mindsets as well as their own definitions of ingroups and outgroups.…”
Section: Mindset Associated With Extremismmentioning
confidence: 88%
“…Attitudes toward others are one of the most researched constructs in the social sciences [75][76][77][78][79][80]. Extensive research demonstrated the effects of positive attitudes toward others [81,82] as well as the effects of negative ones [83][84][85].…”
Section: Attitudes Toward Peoplementioning
confidence: 99%